The etiological role of opportunistic microflora in the pathogenesis of implant-associated inflammation in patients after primary total knee replacement - Babushkina I.V.; Bondarenko A.S.; Ulyanov V.Yu.; Chibrikova Yu.A.; Adilov R.G.; Kupina E.S. (Саратовский научно-медицинский журнал, 2018)
The aim: to study etiological role of opportunistic microflora in the pathogenesis of implant-associated inflammation in patients after primary knee joint replacement and antibiotic sensitivity of main agent groups. Material and Methods. The retrospective analysis of microbiological samples of 383 patients with implant-associated inflammation occurred after primary total knee replacement. Results. Gram-positive cocci (63.5%) are the leading agents of implant-associ- ated inflammation, and there is an increase in the etiological role of coagulase-positive Staphylococci. Main agents of Gram-negative group were Enterobacteraceae and non-enzyme bacteria. We revealed high resistance of Staphylo-coccus spp. to antibiotics of various groups. Oxazolidinones and glycylcyclines were the most active among all antibiotic groups. Gram-negative bacteria were highly resistant to cephalosporine and macrolides with carbapenems and fluoroquinolones being most active. Conclusion. Gram-negative Enterobacteraceae, non-enzyme bacteria and Gram-positive cocci are most significant etiological factors in the pathogenesis of implant-associated inflammation in patients after primary total knee replacement.